Rural Teachers' Perceptions of Their School and Communities - J. David McCracken; Charles Miller (Journal of Research in Rural Education, 1988)
Perceptions of rural secondary teachers about the role of the public school in rural communities were described. Answers were sought for several questions. How do teachers perceive their role in the rural community? What factors help or hinder the teachers in fulfilling their roles? How do the community and school interrelate? What are the expectations of the community for its teachers? Qualitative research methods were used to interview teachers and summarize the results of the interviews. Results indicated that: most teachers preferred the rural school as a place to work, some teachers found it difficult to adapt to the traditional rural community structure, administration wassomewhat informal, assistance with extracurricular activities was expected, second jobs were held by many, and many failed to recognize the importance of agriculture in the economy of the rural community